Komunikasi Antarbudaya di Pondok Pesantren (Studi Kasus di Pondok Pesantren Putri Miftahul Ulum Banyuputih Lumajang) - Rachman , Rio Febriannur; Ilmaniya , Solehati (Al-Insyiroh: Jurnal Studi Keislaman, 2020)
This article discusses intercultural communication in Islamic boarding schools. Islamic boarding school is a religious-based education center which has a dormitory where students stay. They come from various backgrounds. The phenomenon of intercultural communication in there, is interesting to be observed. The purpose of this study is to explain how the patterns, behavior, and barriers of intercultural communication in Islamic boarding schools. This research uses a qualitative method, with a case study approach. The research location is Miftahul Ulum Banyuputih Lumajang, Female Islamic Boarding School. This study collected data by field observations on 8 March to 16 March 2020. In addition, in-depth interviews are also conducted with two religious teachers or administrators and three female students from Madura, Sumatra and Java. Data analysis is performed by reducing, presenting, and formulating conclusions. The results of this study are, first; student maintain mutual ethics in behaving in communication, second; communication patterns between students are generally two-way communication, whereas if student are dealing with Ibu Nyai (caretaker of the Islamic Boarding School) or religious teacher, they will use a one-way communication, third; a striking barrier in the communication process is the semantic or language barrier. To be able to overcome the language problem at the Islamic Boarding School, the students always ask the other students or teachers in Bahasa. This research is expected to be able enrich the research treasure about intercultural communication in Islamic boarding schools.